Establishment of the Customer Perspective of the Balanced Scorecard System at Sports Enterprises Through the Example of a Hungarian Football Club - Lakatos, Vilmos; Erdey, László; Szűcs, Norbert; Rózsa, Attila; Nagy, Adrián (Applied Studies in Agribusiness and Commerce, 2019)
In our present world, more and more attention is being paid to the evaluation and monitoring of different sports organizations, which is because the support of spectator sports has become an important issue. Our fundamental assumption is that football clubs of our time should operate just like large companies in the business sectors. Obviously, it is an essential prerequisite that controlling, a controlling system or a performance measurement system be applied at the business entities operating the clubs. According to our experience, conscious financing of organizations is often neglected in the course of the management processes of sports companies. It is necessary to create the conditions at these organizations that enable managerial decision support and the establishment of a controlling system. It is essential to find controlling methods and tools that can be successfully applied in the life of a sports organization and that ensure the harmonization and coordination of different processes. Consequently, controlling provides a higher level of transparency and information supply for decision makers. The aim of present study is to introduce the Balanced Scorecard (The Balanced Scorecard is a balanced strategic system of indexes, which measures the performance of companies for the sake of implementing the strategy), one of the tools of strategic controlling and its application to sports companies through an example of a Hungarian football club. JEL Classification: Z23